Ex Post Impacts of Improved Maize Varieties on Poverty in Rural Ethiopia - Zeng, D.; Alwang, J.; Norton, G. W.; Shiferaw, B.; Jaleta, M.; Yirga, C. (Wiley, 2015)
This Agricultural Economics journal article (http://onlinelibrary.wiley.com/doi/10.1111/agec.12178/full) is based on the study that documents the impacts of improved maize varities on household well-being and on overall rural poverty using primary data. In Ethiopia, the last four decades have seen more than 40 improved varieties of maize - including hybrids and OPVs – developed and released by the Ethiopian Institute of Agricultural Research (EIAR) in collaboration with the International Maize and Wheat Improvement Center (CIMMYT). An Impact Brief (#45) (http://impact.cgiar.org/sites/default/files//pdf/SPIA_Impact-Brief-45_Dec2014.pdf) based on the report/study submitted to SPIA is also available. The full report will be published shortly on this site along with the SPIA foreword.